KEPENTINGAN INDONESIA MELAKUKAN KERJASAMA DENGAN JEPANG DALAM BIDANG PERTAHANAN MILITER DALAM PERJANJIAN 2+2 (ANALISIS DIPLOMASI PERTAHANAN) - Rizqa Deni Fathanah; Saiman Pakpahan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This study aims to analyze Indonesia's interests in carrying out defense cooperation with Japan on the 2+2 nomenclature. This defense cooperation involves two ministries from each country; the Ministry of Defense and Ministry of Foreign Affairs. Furthermore, the collaboration began in 2015 and will continue in 2021. To maintain the analytical framework, this study uses a qualitative methodology supported by interviews with structural experts and related officials, document analysis, literature studies, and policy observations. The aspect of International Relations in this research lies in the use of Neorealism and Defense Diplomacy perspectives as a theoretical framework. The correlation between the two leads to the results of academic observations in this study. This research found rational reasons for why the collaboration occurred, the reasons for its urgency, and its relevance. Broadly speaking, this study found the driving factors for cooperation between Indonesia and Japan in 2+2 due to the similarity of challenges and threats between Japan in East Asia and Indonesia in Southeast Asia. In addition, inter- and intra-regional complexity is one of the cornerstones of the analysis. Keywords: Indonesia and Japan 2+2 defense cooperation, Indonesian defense diplomacy, dynamics of the strategic environment.